Porous Carbon Networks Decorated with Cobalt on CoFe2O4 as an Air‐Breathing Electrode for High‐Capacity Rechargeable Lithium‐Air Batteries: Role of Metallic Cobalt Nanoparticles. Issue 20 (1st September 2020) - Athika, Mattath; Elumalai, Perumal
Abstract: The development of cost‐effective efficient bifunctional electrocatalysts for metal‐air batteries is an important aspect for its commercialization. We demonstrate the effect of Co nanoparticles and/or the porous carbon matrix in pristine CoFe2 O4 (CFO) electrocatalysts towards the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). The Co/CoFe2 O4 ‐carbon network (CCFOC) with a high surface area and good conductivity offered more active sites for oxygen adsorption as well as accelerated electron transfer kinetics, leading to superior ORR and OER activities. A Li‐air battery split cell was fabricated using the CCFOC as an air‐breathing electrode, which exhibited a high discharge capacity of 4320 mAh g −1 at a high current density of 100 mA g −1 with an acceptable cycling stability and columbic efficiency. The fabricated coin cell or the split cell Li‐air battery could power a commercial 2.8 V green LED bulb continuously for more than 6 h. Abstract : Take a breath : CoFe2 O4, Co/CoFe2 O4 and Co/CoFe2 O4 ‐decorated porous carbon networks are synthesized by means of a facile one‐spot combustion synthesis and used as air‐breathing electrocatalysts. The effect of Co metal nanoparticles and/or the porous carbon matrix with pristine CoFe2 O4 electrocatalyst towards the oxygen reduction reaction and the oxygen evolution reaction is examined. The CCFOC catalyst exhibits the highest performance. The fabricated conventional Li‐air battery split cell exhibits a high discharge capacity of 4320 mAh g −1 at a high current density of 100 mA g −1 .